2003
DOI: 10.1074/jbc.m303925200
|View full text |Cite
|
Sign up to set email alerts
|

Glycation Induces Formation of Amyloid Cross-β Structure in Albumin

Abstract: Amyloid fibrils are components of proteinaceous plaques that are associated with conformational diseases such as Alzheimer's disease, transmissible spongiform encephalopathies, and familial amyloidosis. Amyloid polypeptides share a specific quarternary structure element known as cross-␤ structure. Commonly, fibrillar aggregates are modified by advanced glycation end products (AGE). In addition, AGE formation itself induces protein aggregation. Both amyloid proteins and protein-AGE adducts bind multiligand rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
183
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(193 citation statements)
references
References 70 publications
8
183
1
1
Order By: Relevance
“…The presence of β-amyloid like fibril in CuBSAG or 3ZnBSAG structures could explain their relative cytotoxicity for microglia cells. Several previous studies have already highlighted this β-amyloid cytotoxicity of glycated albumin [8,10]. We can also notice that the partial conversion of secondary structure from α-helix into intramolecular β-sheets is rather promoted by the sole incubation at 37°C than the glycation process.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The presence of β-amyloid like fibril in CuBSAG or 3ZnBSAG structures could explain their relative cytotoxicity for microglia cells. Several previous studies have already highlighted this β-amyloid cytotoxicity of glycated albumin [8,10]. We can also notice that the partial conversion of secondary structure from α-helix into intramolecular β-sheets is rather promoted by the sole incubation at 37°C than the glycation process.…”
Section: Discussionmentioning
confidence: 60%
“…Conversely, in the presence of Cu(II) ions, aggregation and glycation appear to be rather competitive processes. If previous studies have demonstrated that aggregation was a process normally associated with glycation [8][9][10], we have also established that glycated albumin loses its capacity to selfassembly into aggregates following thermal process [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse effect of LB extract on heme degradation and conformational alteration of Hb originates from its controlling action on the β-amyloid structure formation. A feature of glycated proteins is the propensity to condense into amyloid fibrils, which are characterized by a specific quaternary structure element known as cross-β structure [41]. In contrast to the holo structure, removal of the prosthetic group from many proteins results in apo forms which commonly leads to the formation of the amyloid structure [29].…”
Section: Resultsmentioning
confidence: 99%
“…[25][26][27][28] AGEs-damaged proteins are highly reactive and become cross-linked, structurally altered, and ultimately aggregated, and these non-native states are toxic for many cell types (e.g., endothelial, neuronal, retinal, leukocytes) and associated with advanced diseases. 29 However, in the manufacturing of therapeutic recombinant antibody products, AGEs formation has not been observed at significant amounts, even with low 21 or high levels of glycation. 8 For therapeutic mAbs, the potential effects of glycation, such as blocking the biologically functional site or further degradation that induces aggregation, make glycation a potential critical quality attribute (CQA).…”
Section: Introductionmentioning
confidence: 99%